Interaction between the Human Hippocampus and the Caudate Nucleus during Route Recognition - Voermans, Nicol C.; Petersson, Karl Magnus; Daudey, Leonie; Weber, Bernd; van Spaendonck, Karel P.; Kremer, Hubertus P.H.; Fernández, Guillén (Neuron (Cambridge, Mass.), 2004)
Navigation through familiar environments can rely upon distinct neural representations that are related to different memory systems with either the hippocampus or the caudate nucleus at their core. However, it is a fundamental question whether and how these systems interact during route recognition. To address this issue, we combined a functional neuroimaging approach with a naturally occurring, well-controlled human model of caudate nucleus dysfunction (i.e., preclinical and early-stage Huntington's disease). Our results reveal a noncompetitive interaction so that the hippocampus compensates for gradual caudate nucleus dysfunction with a gradual activity increase, maintaining normal behavior. Furthermore, we revealed an interaction between medial temporal and caudate activity in healthy subjects, which was adaptively modified in Huntington patients to allow compensatory hippocampal processing. Thus, the two memory systems contribute in a noncompetitive, cooperative manner to route recognition, which enables the hippocampus to compensate seamlessly for the functional degradation of the caudate nucleus.